Promoting healthy lifestyles through youth activity participation: Lessons from research on the developmental impacts of movement-based programs. - Johnson, Sara K. ; Agans, J. P.; Champine, R. B.; Erickson, K.; Yalin, C. (Tufts University. Tisch Library., 2016)
The goal of this chapter is to explain how movement activity settings can contribute to young people’s positive youth development (PYD) and continued participation in these types of activities throughout their lives.